What does it mean to respect? A semantic sketch - Lisczyk, Karolina (Papers in Linguistics, 2020)
The purpose of the article is to determine what contemporary Polish users mean when they use the word to respect. The article discusses its past and present meanings. The author undertakes a lexicographic review, collates the previous findings of various researchers, and also analyses material excerpted using the corpus search engine. Another aspect which is addressed is the meaning of commonly used phrases with the verb to respect. Methodologically, the work is based on the assumptions of lexical semantics.